Сreating comic effect by means of word formation (linguistic sense of ostap vyshnya) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article deals with the comic verbal means in the works of Ostap Vyshnya. This paper confirms conscious word standards violation and describes the creation of humorous, satirical, ironic effects due to the usage of stylistic structural word means. Ostap Vyshnya produces “comic” words (similar to existing words) indicating the action (derived from occupation, profession, place of the performance etc.), the subject concepts, marking nominations by means of adding affixes to initial words that do not correspond to the norms of Ukrainian literary language.This research shows that the humorist tends to certain condensation in the semantics of his poetic language and using the bookish models, he actively creates difficult for pronounciation units, so called his own style of “derivation parody”. Thanks to excessively complicated structure such language units consisting from several stems and affixes dim their primary lexical meaning and become pun words. Ostap Vyshnya is aware of the idea that comic effects reduce the distance in the interpersonal communication, uncover the hidden irony and help in percepting jokes. Above mentioned writer, ridiculing ignorance in sciences, supplies pseudoetymological interpretation with pseudocommentary. The conscious use of false motivations, interpretation and pseudoetymology is a defining feature of Ostap Vyshnya’s poetic style.
Keywords: word formation means creating comic effects; derivation standard; word formation method; false motivation; pseudoetymological interpretation